2009
DOI: 10.1159/000258668
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Neurobiology of Feeding in the Opisthobranch Sea Slug, <i>Aplysia</i>, and the Pulmonate Snail, <i>Helisoma</i>: Evolutionary Considerations

Abstract: The motor systems that generate feeding-related behaviors of gastropod mollusks provide exceptional opportunities for increasing our understanding of neural homologies and the evolution of neural networks. This report examines the neural control of feeding in Helisoma trivolvis, a pulmonate snail that ingests food by rasping or scraping material from the substrate, and Aplysia californica, an opisthobranch sea slug that feeds by using a grasping or seizing motion. Two classes of neurons that are present in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 110 publications
(103 reference statements)
0
29
0
Order By: Relevance
“…Further studies should explore whether the OA li cells of Aplysia function in a capacity that is similar to the OC cells of Lymnaea and N3a cells of C. Martínez-Rubio, G. E. Serrano and M. W. Miller Helisoma, i.e. as CPG elements that drive a hyper-retraction phase of motor activity (see Murphy, 2001;Wentzell et al, 2009). Alternatively, distinct roles of the Aplysia OA li neurons could reflect their contributions to modifications of circuit performance that have occurred in response to evolutionary pressures on ) resulted in both B67s becoming highly rhythmic.…”
Section: Localization Of Oa LI In Aplysiamentioning
confidence: 99%
“…Further studies should explore whether the OA li cells of Aplysia function in a capacity that is similar to the OC cells of Lymnaea and N3a cells of C. Martínez-Rubio, G. E. Serrano and M. W. Miller Helisoma, i.e. as CPG elements that drive a hyper-retraction phase of motor activity (see Murphy, 2001;Wentzell et al, 2009). Alternatively, distinct roles of the Aplysia OA li neurons could reflect their contributions to modifications of circuit performance that have occurred in response to evolutionary pressures on ) resulted in both B67s becoming highly rhythmic.…”
Section: Localization Of Oa LI In Aplysiamentioning
confidence: 99%
“…Larvae feed on a solid diet made of cattle manure, hay, and other waste materials on the ground, whereas the adults are obligate blood feeders of animals and humans. Feeding behaviors and the physiological and molecular mechanisms that control feeding have been investigated in several invertebrate models, including the pond snail, Lymnaea stagnalis (Rose and Benjamin, 1981;Staras et al, 1998;Straub et al, 2002), and the sea slug, Aplysia californica (Rosen et al, 2000;Evans et al, 2005;Wentzell et al, 2009). Feeding musculature, neuronal circuits involved in the control of feeding, and the pharmacological modulation of feeding behaviors have also been investigated in detail in a few insect species, including locusts Bräunig, 1997, 2001;Zilberstein and Ayali, 2002;Ayali, 2004), the adult tobacco hornworm (Miles and Booker, 1998;Ayali, 2004), the adult blowfly (Gelperin, 1967(Gelperin, , 1972Fredman and Steinhardt, 1973;Starre and Ruigrok, 1980;Mier et al, 1985;Bowdan and Dethier, 1986), and blowfly larvae (Schoofs and SpieX, 2007;Schoofs et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Much of the work conducted in this and other molluscan systems has focused on motor systems, especially motoneurons controlling the buccal feeding apparatus and radula (Murphy, 2001; Elliott and Susswein, 2002; Wentzell et al ., 2009). Murphy and Kater (1978) demonstrated that after axotomy, motoneurons within the buccal ganglia of Helisoma undergo extensive regeneration and finally reinnervation of their normal target organs.…”
Section: Introductionmentioning
confidence: 99%